Pedagogy and Psychology of Modern Education - Iudin G. V., Krasovskaia S. V., Vasiagina T. N., Gorbatov I. A., Ryzhova I. M., Samigullina G. S., Dzokaeva Z. M., Zainullin L. I., Kochetkova T. N., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Prozorova M. N., Boiko A. V., Sesorova L. N., Gani S. V., Konstantinova N. I., Kvitatiani S. V., Zhaldak N. N. (Pedagogy and Psychology of Modern Education, 2023)
at the St. Petersburg International Economic Forum (PIEF–2023), the President of the Russian Federation V.V. Putin presented a new concept for the development of a country with a sovereign economy. This time, the president did not as much emphasize and highlight priorities, as he summarized the theoretical and methodological basis for the announced model. The President answered the fundamental question: how and in what way will the new Russian economy be built – «the economy of supply». We are talking about the transition to a qualitatively new level of development – to a sovereign economy that not only reacts to market conditions and takes into account demand, but also forms this demand. Such an economy is often called the «supply economy» and presupposes a large-scale increase in production forces and the expansion of the service sector, the widespread creation of new modern industrial facilities and entire industries, including in those areas "... where we have not yet proven ourselves properly, but there are scientific opportunities, creative potential that we have, of course» – that's how V.V. Putin described the contours of the new development model. The main principles will be: orientation of the education system on employment of graduates; expansion of entrepreneurial activity; increasing the attractiveness of Russia as a state of central jurisdiction for conducting global business and preventing the transfer of funds from the country abroad; ensuring investment growth; maximum spread of the «lean production» system; automation and mastering of artificial intelligence (AI) technologies. Experts named the immediate «builders of the country's technological sovereignty»: to achieve it, experts in artificial intelligence, blockchain and robotics will be needed.
Keywords: искусственный интеллект; реформа образования; artificial intelligence; блокчейн; дроны; blockchain; the Fourth Industrial Revolution; роботизация; модель развития России; реформа образования в год педагога и наставника 2023; Четвёртая промышленная революция; авиамодели; квадрокоптеры; обучение полётам; новые предметы в школе; уроки труда в школе; Russia's development model; education reform in the year of the teacher and mentor 2023; education reform; robotic automation; aircraft models; drones; quadrocopters; flight training; new subjects in school; labor lessons at school